IMPLEMENTATION OF CMMI IN MEASURING THE PERFORMANCE OF THE WASTE BANK INFORMATION SYSTEM DEVELOPMENT PROJECT IN KELURAHAN DURI KEPA JAKARTA BARAT - Fajriah, Riri; Meiyanti, Ruci (IJISCS (International Journal of Information System and Computer Science), 2024)
The goal of CMMI (Capability Maturity Model Integration) adoption in project performance measurement is to enhance and optimize the Waste Bank Information System project's development process. Through the adoption of the CMMI's best practices and principles, the project team can increase the productivity and efficiency of project implementation. With improved risk identification and management, the project is less likely to encounter difficulties or fail. This is made possible by CMMI. The GAP Analysis assessment stage of the research process is used to determine how well Duri Kepa Village has followed the CMMI process. Next, the project's goals and scope are established. Finally, the CMMI process is mapped to the stages of implementation and process modifications in accordance with CMMI practices, as well as the process of performance monitoring and measurement. The aim of this study is to improve the project completion predictability for the Waste Bank Information System design and implementation in Duri Kepa Village. The project team will be better equipped to plan, coordinate, and manage project resources in order to promote project success by putting CMMI standards into practice.